Effect of N-acetylcysteine on craving in substance use disorders (SUD): a meta-analysis of randomized controlled trials - Cuocina, Micol; Aiello, Giuseppe; Cutrufelli, Pierfelice; Rampello, Martina; Rapisarda, Laura; Rodolico, Alessandro; Cantarella, Giuseppina; Signorelli, Maria Salvina; Bernardini, Renato (Frontiers in Pharmacology, 2024)
Background N-acetyl cysteine (NAC) appears promising as a treatment in patients with substance use disorder (SUD) as it helps rebalance glutamate levels in the central nervous system (CNS). Basal concentrations of glutamate are indeed reduced in SUD patients but increased during craving. Materials and Methods We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs). We assessed whether NAC reduce craving rating as compared to a placebo in SUD patients. Secondary outcomes were withdrawal symptoms (WS), side effects (SE) and drop-outs. Estimates are presented as standardized mean differences (SMD) or risk ratio (RR) with 95% confidence interval (CI). Results Eleven RCTs were included. NAC reduced craving rating (SMD -0.61 (−1.17, −0.06), p = 0.03, I2 = 85%), with no differences in the subgroup analysis according to the drug addiction (alcohol, cocaine, poly-drugs, amphetamine, nicotine) (p = 0.98). Among the secondary outcomes, for WS data showed no significant difference between groups (SMD -0.18 (−0.43, 0.08), p = 0.17); for SE no substantial difference was observed between the two treatment groups (RR = 1.06 (0.89–1.27), p = 0.52, I2 = 0%); for dropouts the results are in favor of the placebo but no statistically significant (RR 1.17 (0.85, 1.61), p = 0.34; I2 = 0%). Conclusion NAC seem to reduce craving rating in SUD patients, but evidence is weak. More studies are needed to confirm this finding.